Strategi Peningkatan Daya Saing UMKM melalui Manajemen Usaha, Digital Marketing dan Branding - Rahman, Abdul; Amalia, Ade; Rosnaida, Rosnaida; Japina, Henky (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity aims to enhance the capacity of MSME actors in Sumber Padi Village through training in business management, digital marketing, and branding strategies. The method employed an integrated approach consisting of several stages, including socialization, interactive training, hands-on practice, and pre- and post-activity evaluation. Interview results showed an increase in participants’ average ability from 26.4% to 76.0%, or a 49.6% improvement after the training. The program had a positive impact on participants’ digital literacy and marketing strategies. As a follow-up, the Sumber Padi Digital MSME Community was established, and the development of the “Sumber Padi Digital Corner” is planned as a center for digital-based business promotion and consultation. This activity is expected to strengthen the village’s competitiveness and economic independence.